Analisis Kemampuan Pemahaman Konsep Matematis Siswa pada Materi Relasi dan Fungsi melalui Model Problem Based Learning (PBL) di Sekolah Menengah Pertama - Basar, Acamina; Ratuanik, Mesak; Watratan, Yoseph (Polinomial : Jurnal Pendidikan Matematika, 2026)
Conceptual understanding is a fundamental ability in mathematics learning; however, it remains a challenge for eighth-grade students of SMP Negeri 5 Wermaktian on the topic of relations and functions. This study aimed to analyze students’ mathematical conceptual understanding through the implementation of the Problem Based Learning (PBL) model. The study employed a qualitative approach with a descriptive design. The research subjects consisted of 17 eighth-grade students. Data were collected through pre-tests, post-tests, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicated that the implementation of the PBL model improved students’ mathematical conceptual understanding. Students became more actively involved in the learning process, were able to relate mathematical concepts to contextual problems, and constructed conceptual understanding independently through group discussions. Thus, the PBL model contributed positively to enhancing students’ mathematical conceptual understanding on the topic of relations and functions.